1994
DOI: 10.1164/ajrccm.149.6.8004303
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of thromboxane A2 in propranolol-induced bronchoconstriction after allergic bronchoconstriction in guinea pigs.

Abstract: Although it is well recognized that beta-blockers can induce bronchoconstriction only in patients with asthma, mechanisms of the bronchoconstriction are not well known. We hypothesize that bronchoconstriction induced by beta-blockers may result from inflammatory mediators released by allergic reactions. In this study, we developed a guinea pig model for propranolol-induced bronchoconstriction (PIB) after antigen inhalation and investigated the effect of specific thromboxane (TXA2) receptor antagonists, S-1452 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…It adds to the list of mediators that may be involved in the PIB. However, the contribution may be relatively small because the degree of inhibition of the PIB was smaller with the PAF antagonists used in this study than with TxA 2 antagonists examined in our previous study [5]. As PAF levels in bronchoalveolar lavage fluid (BALF) or bronchial tissues were not measured after the response, we do not know the detailed mechanism of the role played by PAF in the development of PIB in our animal model.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…It adds to the list of mediators that may be involved in the PIB. However, the contribution may be relatively small because the degree of inhibition of the PIB was smaller with the PAF antagonists used in this study than with TxA 2 antagonists examined in our previous study [5]. As PAF levels in bronchoalveolar lavage fluid (BALF) or bronchial tissues were not measured after the response, we do not know the detailed mechanism of the role played by PAF in the development of PIB in our animal model.…”
Section: Discussionmentioning
confidence: 82%
“…However, no correlation was found between the degree of bronchodilation provoked by terfenadine and the magnitude of the decrease in responsiveness to propranolol [23]. Our previous study [5] revealed that TxA 2 may also play an important role in the pathogenesis of this reaction. In addition, a recent preliminary study from our group [11] showed that a 5-lipoxygenase inhibitor, AL3264, inhibited the PIB developed after allergic reaction, leading us to examine the role of another lipid mediator, PAF, in the PIB.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations